ANALISIS KEUANGAN PT. GAJAH TUNGGAL DENGAN METODE PERHITUNGAN RETURN ON ASSETS (ROA) BERBASIS WEB - Muhammad Bachtiar Liosa Putra; Hadi Sucipto (Fakultas Teknologi Informasi, 2024)
This research aims to develop company financial analysis using the Return On Assets calculation method.The background of this research refers to the financial report data of PT Gajah Tunggal in 2023 which hasbeen attached to the official website which can be accessed, but here the problem is that the financialinformation data has not yet determined the percentage of their financial effectiveness in detail so thatpotential investors or prospective investors do not get information quickly so they have to calculate itmanually themselves so it is not effective for translation, so this research is aimed at making automaticcalculations for all the calculations needed by a potential investor or prospective investor, where thissystem can calculate the Return On Assets value and other calculations automatically and can be printed asa detailed report. Based on the researcher's experiments and implementation, it was concluded that theReturn On Assets calculation method and other calculation methods that were applied were successful inproviding accurate calculation results and in all experiments the calculation accuracy was very precise ascompared to the manual calculations that had been carried out. This system is running well according to thedesign that has been carried out with data that has been obtained from PT Gajah Tunggal's financial data,where the data is the annual financial data published for financial data in 2023.Keywords: Financial analysis, PT Gajah Tunggal, Return On Assets calculation method.